Study of periodically loaded metamaterial transmission lines - Wong, Samuel Peng Wui. (2010)
Today, there is an increase in the development of wireless communication systems. These systems are developed in such a way that they are able to support a wide variety of networks services. However, in midst of this development, there are still demands that are strongly emphasized. These demands that are strongly emphasized are the needs for compactness and faster data transfer rate. Therefore, in order to meet these demands, the study of the periodically loaded metamaterial transmission line is necessary in the microwave community. In this project, there are different matrix representations being introduced. Examples of the matrix representations being introduced are the impedance (Z), Admittance (Y), Scattering (S) and the ABCD matrix representations. Also in this project, a metamaterial known as the Left-Handed (LH) material is also being introduced. It exhibits unique properties such as the inverted Snell‟s Law, the Doppler shift and the Cherenkov radiation. Although its circuit model do not exist in nature, due to the fact that it has LH properties as well as Right-Handed (RH) properties, it can be represented as a general composite right/left-handed (CRLH) transmission line (TL) model. Therefore, based on this general CRLH TL model mentioned, the balanced CRLH lossless TL model and its dispersion diagram can be presented. In this project, the LC-based CRLH lossless TL model is considered. By cascading these TL models together, under the homogeneous case, a CRLH lossless TL model of a definite length can be presented in this report. Also, its dispersion diagram for the balanced and unbalanced case can be represented in this report as well. Also, in this project, a specific filter application known as the composite right/left-handed coplanar waveguide bandpass filter is considered. Its design, implementation and specifications are also considered in this project as well. In this project, the plot for the unbalanced dispersion diagram for the LC-Based CRLH TL model is verified. By considering the TL model as a cascade of different networks, using the specifications of the substrate, the plot is verified. However, for the design of the bandpass filter, the redesign needs further tuning. It is only through tuning that its specifications can then be met.